CORRELATION AMONG PERSONALITY AND SELF-CONCEPT TO STORYTELLING ABILITY - Istnain Alfajri Husain; Aris Suziman (Universitas Sulawesi Tenggara, 2020)
Abstract: This research aimed to determine the Correlation of (1) the personality to storytelling ability, (2) self-concept to storytelling ability, (3) personality and self-concept together to storytelling ability. This research was conducted in TK B Islam Kemaraya, TK B Mekar Indah Kendari and TK B Aisyiyah Kendari. The data analysis techniqueus is the multiple correlation analysis. The results showed that there is a correlation of (1) the personality to storytelling ability, (2) self-concept to storytelling ability, (3) personality and self-concept together to storytelling ability.This implies the storytelling ability can be improved by enhancing personality and self-concept.Keyword: personality, self-concept, Storytelling ability